64Hz induction magnetometer data for Husafell in CDF - Kazuo Shiokawa; ISEE IUGONET Metadata Management Group (名古屋大学, 2017)
The induction magnetometer data observed at Husafell, Iceland. The data consist of variations of three-dimensional (H, D, and Z components) geomagnetic field taken with a sampling rate of 64 Hz, and some engineering parameters for the instrument, such as the sensitivity and phase difference. The digital data are distributed in the Common Data Format (CDF) through the ERG-SC repository. Importnat Notes: 1. For frequencies below ~1Hz, use the following equation to obtain amplitude values in units of nT/s: dB/dt (nT/s) = data (V) / quick_sensitivity. The value of quick_sensitivity is given in global attributes. For frequencies above ~1Hz, use the exact sensitivity curve to obtain absolute amplitude of waves. 2. Please note that the positive direction (polarity) of H, D, and Z are different depending on the station. For example, in February 2011, the polarity is GAK: positive=northward, eastward, upward; MGD: positive=northward, eastward, downward; ATH: positive=northward, eastward, downward; MSR: positive=southward, westward, upward; STA: positive=northward, eastward, downward. Please see http://stdb2.isee.nagoya-u.ac.jp/magne/magne_stations.html for the latest information. dataset